Characterization of Lipase-producing Haloarcula Strain from Thai Fish Sauce - Sirilak Namwong (Science Faculty of Chiang Mai University, 2019)
An extremely halophilic strain HST01, from Thai fish sauce, grew optimally at 37 °C, pH 7.0 and in the presence of 20-25%, w/v NaCl, was screened for lipase activity. Phylogenetic analysis based on the comparison of 16S rRNA gene sequence revealed that strain HST01 was closely related to Haloarcula argentinensis JCM 9737T (99.7% similarities). On the basis of the phenotypic and chemotaxonomic characterizations including DNA–DNA relatedness (84.1-98.5%). It was identified as Haloarcula argentinensis JCM 9737T. The strain HST01 produced lipase (3.0 U/ml) in standard medium and the twofold increase of lipase activity was observed, 6.2 U/ml, in response to supplementation of palm oil in the basal medium. In addition, lipase production was evaluated (5.0 U/ml) in the presence of inexpensive and renewable lipase inducer, cooking palm oil. Therefore, strain HST01 might be used for the biotechnological applications such as food processing, environmental bioremediation and biosynthetic processing interesting for further studies.